Decision-making and acute behavioural disturbance (ABD): a qualitative thematic analysis of perspectives on decision-making by UK ambulance paramedics - Jaqualine Lindridge; Timothy Edwards; Leda Blackwood (BMC Emergency Medicine)
Abstract Background Incidents involving severe agitation are complex emergencies which occur infrequently in the community but have high stakes for patients and responders. Acute behavioural disturbance (ABD), an umbrella term used to describe severe agitation, sometimes known as excited delirium, affects patients who typically present to police and ambulance paramedics and may require restraint. However, little is known about how paramedics make these restraint decisions. This research aimed to explore the decisions made by paramedics when managing restraint in the context of ABD in the UK ambulance setting. Methods Ten semi-structured interviews and one focus group were undertaken with one newly qualified and 12 experienced paramedics employed by a large metropolitan ambulance service. The resulting data were analysed using reflexive thematic analysis, informed by critical realism. Results We identified three interrelated themes from the data: working in the context of fear, navigating complexity without consistent and adequate formal subject-specific training, and the nature of professional roles and relationships at incident scenes. These restraint decisions are a source of concern, with paramedics fearing patients coming to harm and the potential for detrimental professional repercussions. Decision-making was complicated by mismatched levels of education specific to restraint and the management of ABD patients, and the requirements of ‘real world’ clinical practice. The social relationships between paramedics and others at incident scenes were also important, with paramedics situating ABD incidents as healthcare rather than law enforcement encounters key to influencing restraint decisions. Conclusions Our results indicated that paramedics would benefit from further education which is specific to identifying and managing the complex social interactions which occur at ABD scenes. High-fidelity simulation training delivered jointly with other agencies may be a helpful intervention in achieving this.